Avaliação da alteração de propriedades ópticas, mecânicas e efeitos adversos de clareadores over-the-counter - Oliveira, Murilo Navarro (2024)
Over-the-counter (OTC) products appeared in the early 2000s in the United States as an alternative for patients who could not afford a dentist but sought bleaching treatments. These products have a low hydrogen peroxide concentration and may be sold without a prescription from a dental professional, depending on the legislation of each country. The literature includes several clinical and laboratory studies using OTC products, showing they effectively change the color of dental elements. However, it lacks a review that may use all described products to compare color changes and whether they promote color changes similar to conventional bleaching. The general objective of this thesis is to assess the efficacy of OTC bleaching agents in changing the optical and mechanical properties of teeth, identifying potential adverse effects. Specific objective 1: To perform a systematic review of randomized clinical trials to assess color changes and adverse effects of OTC bleaching agents. Specific objective 2: To asses in vitro the impact of OTC products on the optical properties (color and gloss changes) of bovine teeth subjected to a simulated orthodontic treatment. Specific objective 3: To asses in vitro the impact of OTC products on the mechanical properties (surface roughness and shear) of bovine teeth subjected to a simulated orthodontic treatment. The analyzed data concluded that: 1) OTC products achieved satisfactory color change outcomes with little or no impact on tooth sensitivity, but the studies presented a low certainty of evidence. 2) Except for dentifrices with peroxide, the tested OTC bleaching agents presented color change outcomes similar to in-office bleaching. Gloss did not change in any group. 3) The tested OTC products did not influence the mechanical property outcomes of teeth subjected to a simulated orthodontic treatment.